(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the study is to identify the relationship between doppler parameters and perinatal outcomes in post-term pregnancies.Material and Method: 101 pregnant women (37-41 weeks, control group; n:51 and ≥41 weeks, study group, n:50) were included in the study. We performed umblical artery and middle cerebral artery blood flow velocity waveform (pulsatility index, resistivity index, and systole/diastole ratio) analyses for our patients.Results: The mean value of the umbilical artery resistivity index was significantly higher in the study group than the control group while the mean value of the umbilical artery pulsatility index was significantly lower in the study group. The middle cerebral artery resistivity index was significantly lower in the study group, which was consistent with preferantial perfusion of the brain. We also found decreased ratios of middle cerebral artery resistivity index in umblical artery resistivity index in the study group (1.11) compared with the control group (1.25). These findings can be interpreted in favor of worse perinatal outcomes in the study group while the increased adverse perinatal outcome rates (%64) in the study group supports this view. The ratio of middle cerebral artery resistivity index to umblical artery resistivity index 1.155 can be used as a sign of adverse perinatal outcomes in prolonged pregnancies with a senstivity of %76.6 and a specificity rate of %85.2.Conclusion: Doppler ultrasonography can be used for reducing perinatal mortality and morbidity of prolonged pregnancies